녹차 수급안정 및 경쟁력 제고방안 - 박문호 (한국농촌경제연구원, 2008)
The green tea industry in Korea has been growing steadily in the last 10 years as consumers are laying more stress on well-being of themselves. However, due to the recent wider market opening and changing consumption patterns, the balance between demand and supply is in great danger. The purpose of the study is to make strategies to increase the competitiveness of the Korean green tea industry and to stabilize the domestic market as well. In Korea, the area to grow green tea leaves has been expanded about four times and the production has increased more than five times during the last ten years. China experienced 1.3 times increase of growing area and 1.7 times increase of production during the same period. Meanwhile, in Japan, the area has decreased and the production was about the same. All the major green tea leaf growing countries in Asia has struggled to expand their tea industries. There are four basic rules suggested by us to follow in order to result in more stable tea industry in Korea. First, the size of tea growing area should be controlled properly based on long-term projection of the market by the local government with major tea growing producers. Second, in each growing district, it is necessary to set up organizations consisting of representatives of producers that will control the supply of tea leaves by themselves. Third, in aspect of food safety, it is required to have extensive supervision of import tea products in terms of origin and agricultural practice. There are various tasks to fulfill to improve he competitiveness of Korean tea industry. It is essential to maintain the good quality of tea leaves that are of course produced environment friendly. We also need to foster business activities of core entities in local regions and encourage them to cooperate forward to build a fermented tea processing system. To facilitate high quality tea consumption, along with systematic education of tea serving and promotion of tea consumption, each tea producing district needs to have own unique characteristics and, therefore, to be distinguished to each other. Instead of trying to stay and be protected within the acquainted domestic market, our green tea producers are required to be equipped with high quality product then carry out an aggressive global marketing to challenge world producers. Researchers: Park, Moon-Ho, Kim, Sung-Young, An, Beung-Il and Lee, Moon-Ho Research period: 2007. 8. - 2008. 3. E-mail address: mhpark@krei.re.kr, sungyoung@gnu.ac.kr, ahn@gnu.ac.kr,mhlee@krei.re.kr